Hand hygiene knowledge and demonstrated technique among Malawian kindergarten children: A quasi‐experimental study - Balwani Chingatichifwe Mbakaya; Maggie Zgambo; Fatch Welcome Kalembo (Wiley, 2023)
Abstract Aim To evaluate hand hygiene knowledge and demonstrated technique before and after implementation of the hand hygiene programme and its sustainability among Malawian kindergarten students. Design Quasi‐experimental design, utilizing a repeated measure at three points, namely, before intervention (T0), soon after intervention (T1) and follow‐up (T2). Methods The hand hygiene programme consisted of integrating hand hygiene protocol into the school health curriculum, setting up proper handwashing facilities, training school teachers, health talks and developing reminders on hand hygiene. Fifty‐three kindergarten children aged 3-6 years were enrolled in the programme. Data were collected at 3 months' intervals (T0, T1, and T2). Parents, teachers, school authorities and children were involved in the implementation and evaluation of the intervention, utilizing a multilevel approach. Results There was a significant difference in knowledge scores across three time points (T0, T1 and T2), Chi‐Square (2, n = 53) = 79.02, p < 0.005 and handwashing technique across the three time points, Chi‐Square (2, n = 53) = 88.04, p < 0.005. There was a large effect size of 0.62 on the effect of handwashing technique scores from T0 to T1.